(Invited) Temporary Bonding with Polydimethylglutarimide for Residue-Free Layer Transfer and 3-D Integration. (14th September 2015) - Matsumae, Takashi; Koehler, Andrew D.; Greenlee, Jordan D; Anderson, Travis J; Baumgart, Helmut; Jernigan, Glenn G; Hobart, Karl D; Kub, Francis J
Abstract : Bonding of lift off resist (LOR) was performed to realize temporary wafer bonding without residue. Bonding process conditions such as spin speed, pre-bake temperature, and bonding temperature were optimized to obtain a large bonded area with high bond strength. Under optimized process conditions, a bonded area covering over 98% of the wafer surface, with a room temperature bond strength of nearly 5 J/m2 is achieved. During razor blade testing, fracture often occurs at the Si wafer. Moreover, debonding using an N-Methyl-2-pyrrolidone (NMP)-based solvent left the wafer surface extremely small amount of residue. Thus, the optimized bonding processed developed in this research is suitable for a clean temporary bonding process.